2017
DOI: 10.12693/aphyspola.132.1616
|View full text |Cite
|
Sign up to set email alerts
|

New Porosimetric Method Based on the 3γ Annihilation Rate. Applications to Materials Science and Medical Imaging

Abstract: A new parameter δ based on 3γ annihilation is proposed. It describes the porosity of the materials containing small intermolecular voids below 1 nm. It can be applied to material investigation to compare changes in the material porosity depending on temperature or pressure as well as to study of ageing or manufacturing processes. Particularly it is dedicated to prepare the new imaging method and can be used during positron emission tomography diagnosis allowing determination the kind or stage of pathogenic alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Recently, significant differences in PALS parameters between normal and tumor tissues were also observed by the J-PET group in samples of uterine leiomyomatis and normal myometrium tissues taken from women-patients after surgery [21], [22]. In case of all samples from six patients it was found that mean o-Ps lifetime are of about 2 ns, while for normal tissues this value is of about 50 ps lower.…”
Section: Current Pals Application In Biologymentioning
confidence: 89%
“…Recently, significant differences in PALS parameters between normal and tumor tissues were also observed by the J-PET group in samples of uterine leiomyomatis and normal myometrium tissues taken from women-patients after surgery [21], [22]. In case of all samples from six patients it was found that mean o-Ps lifetime are of about 2 ns, while for normal tissues this value is of about 50 ps lower.…”
Section: Current Pals Application In Biologymentioning
confidence: 89%
“…0.1883 [38] 0.978 [38] 26.22 [39] 5.18 [39] Ionisation energy (eV) [39] measure crystal defects. Recent studies indicating the full utilisation of positronium formation in medicine are also available [13,14]. Studying electron-matter and positron-matter interactions help us answer questions about the structure of matter and the processes they undergo during the collision.…”
Section: Introductionmentioning
confidence: 99%
“…The innovative construction concept was recently proposed by the J-PET collaboration [24][25][26][27][28][29][30][31]. One of the advantages of J-PET is a possibility of multi-photon imaging [32,33] which enables the diagnosis based on positron and positronium lifetime [16] as well as on the ratio of 3γ and 2γ annihilation rates [17,34,35].…”
Section: Introductionmentioning
confidence: 99%